RHETORICAL STRATEGIES IN POLAND’S WOMEN’S STRIKE: THE DIFFUSION OF SEMIOTIC DISOBEDIENCE THROUGH PROTEST BANNERS AND SIGNAGE (Journal of Contemporary Philology, 2024)
This paper presents an exploration of the dynamics of contemporary protest movements in the digital age, focusing specifically on the Women’s Strike protests in Poland. Through its application of sociological diffusion theory, the study investigates the ways in which these movements adopt and adapt protest strategies through the lens of semiotics, language, and cultural references in the context of the Internet's influence. By drawing on various sources, including social media, the paper examines the role of hashtag activism, metaphor, profanity, and cultural tropes in shaping the discourse and symbolic expression of dissent. The globalisation of protest, particularly through the use of English as a lingua franca, is highlighted as a significant aspect of the evolving protest rhetoric in the Polish Women’s Strikes that took place in the years 2016, 2020, and 2021. The analysis reveals a new wave of semiotic disobedience that utilises the linguistic strategies of expressions in English, pejorative language and metaphor to communicate a socially significant message, symbolizing a broader, global political discourse of equality and solidarity that transcends geographical boundaries. This study contributes to the understanding of contemporary protest formations and their diffusion in the digital age, emphasizing the transformative quality that language has in the face of national protest.
Keywords: diffusion theory; discourse; semiotic disobedience; protest